FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (FRAUD) : (Studi Empiris Pada Auditor BPK RI di Jakarta Pusat) - Digdowiseiso, Kumba; Subiyanto, Bambang; Indra Priadi, Jodi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The study aims to analyze the effects of skepticism professional, independency, and competency on ability to detect fraud. Research is conducted on auditors working in the audit board of the Republic of Indonesia in Central Jakarta. The population in this research is an auditor who works at audit board of the Republic of Indonesia in Central Jakarta, the research method used is simple random sampling. Based on the method, which is willing to be a respondent as many as 106 auditors. The data in this research is the primary data obtained through questionnaires. The data analysis method used is statistical analysis in the form of multiple regression tests. Data processed using SPSS v26. The results of this study show that the skepticism professional positively affects the ability to detect fraud. Similarly, the independent has no effect on ability to detect fraud. Meanwhile, competence positively affects the ability to detect fraud.